Billy the kid - "Morpurgo , Michael" (Harper Collins Publishers London, 2002)
Billy the Kid, whose real name was Henry McCarty, was an American outlaw and gunfighter of the Old West1234. He is alleged to have killed 21 men before he was shot and killed at the age of 211. Although he claimed to have killed 21 men, the actual number is likely less than 102. He was found guilty of the murder of Sheriff Brady and was sentenced to hang5. He escaped from jail two weeks before his scheduled execution by killing two deputies5. He is largely considered an inevitable product of disadvantage, misfortune, and the societal dynamics of the Old American West4.
Keywords: Children Fiction